Endoplasmic reticulum stress of astrocytes in paraventricular nucleus of hypothalamus promotes ventricular electrical instability after acute myocardial infarction in rats - Yuhang Yang; Xinmiao Huang; Wenlong Wang; Jingmei Sun; Xin Wang; Chunrui Ji; Xiufen Qu; Dechun Yin (Frontiers in Cardiovascular Medicine, 2025)
IntroductionAstrocytes in paraventricular nucleus of hypothalamus (PVN) promote the occurrence of ventricular arrhythmia (VA) after acute myocardial infarction (AMI). However, the mechanism is unclear. The purpose of this study was to investigate the changes of astrocytes in the PVN after AMI, which is involved in ventricular electrical instability in rats. MethodsThe rats were randomly divided into 4 groups: sham operation (SH), AMI, AMI + Vehicle (4 μl for each), AMI + GSK2606414(PERK phosphorylation inhibitor, 90 μg/4 μl for each). PVN was administered by microinjection.ResultsAfter 24 h, the AMI and AMI + Vehicle groups had substantially greater levels of hypothalamic astrocyte activation, endoplasmic reticulum (ER) stress, and central inflammation (TNF-α and IL-6) compared to the SH group (P < 0.05). GSK2606414 microinjection in hypothalamus had no significant effect on glial fibrillary acidic protein (GFAP) positive cells and their pathologic morphology in PVN of AMI + Vehicle group, but significantly reduced ER stress (PERK/CHOP) in the group, alleviating central inflammation and activation of central neurons (P < 0.05). Cytological studies confirmed this.ConclusionAs a result, 24 h after AMI, PVN astrocytes underwent ER stress via PERK/CHOP pathway, which caused central inflammation, sympathetic neuron activation, and increased ventricular electrical activity instability. GSK2606414 microinjection into hypothalamus decreased sympathetic nerve excitement and VA occurrence in AMI rats by inhibiting ER stress of PVN astrocytes.